Roll For Initiative - Formato, Jaime (Philadelphia : Running Press Kids, 2022)
Twelve-year-old Riley steps out of her older brother's protective shadow and behind the Dungeon Master's screen, running D&D campaigns for her friends and learning to be independent and self-reliant.
new kids book 2023 winter.
Ages 8-13.
Grades 4-6.
Keywords: Dungeons and Dragons (Game) -- Fiction; Fantasy games -- Fiction; Role playing -- Fiction; Siblings -- Fiction; Self-reliance -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Single-parent families -- Fiction; Fiction; Novels